DRIED NATA DE COCO WITH WATER ABSORPTIVITY COMPETING SILICA GEL - Rahmayanti, Handika Dany; Yuliza, Elfi; Amalia, Nadya; Abdullah, Mikrajuddin (Indonesian Physical Review, 2024)
Nata de Coco (NDC) Â is a network of cellulose fibers that traps abundant of water. If a freshly made NDC is dried to remove nearly all trapped water, we will get a very hygroscopic material. This material is potential for making water adsorber that might compete the well known silica gel. NDC was prepared using standard methods and its water absorption was investigated. Dried NDC was used in this study. For comparison, we also investigated the water absorption of several commercial NDC. To determine its business prospects, the water absorption of silica gel was also investigated. The results showed that dried NDC could absorb water vapor comparable to the absorption of commercial silica gel. This suggests that dry NDC has the potential as an alternative water vapor absorber in food packaging. The advantages of the NDC compared to silica gel are safer and environmentally benign, and easily decomposed.